2018
DOI: 10.1002/anie.201802806
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Synthesis of Silicon‐Stereogenic Vinylhydrosilanes by Cobalt‐Catalyzed Regio‐ and Enantioselective Alkyne Hydrosilylation with Dihydrosilanes

Abstract: The strategic carbon-to-silicon substitution at a stereogenic center can produce chiral silanes with significantly improved properties relative to their carbon congeners. We herein report an unprecedented cobalt-catalyzed asymmetric hydrosilylation of unsymmetric alkynes with dihydrosilanes that furnishes silicon-stereogenic vinylhydrosilanes with high regio- and enantioselectivity. The absolute configurations of the products were determined by chiroptical methods in combination with DFT calculations. The synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(46 citation statements)
references
References 80 publications
0
45
0
1
Order By: Relevance
“…[239] In 2018, Huang and co-workers developed a regio-and enantioselective alkyne hydrosilylation with a pybox-cobalt catalyst (101-CoCl 2 ), providing an efficient strategy for the preparation of silicon-stereogenic vinylhydrosilanes (Scheme 86). [239] In 2018, Huang and co-workers developed a regio-and enantioselective alkyne hydrosilylation with a pybox-cobalt catalyst (101-CoCl 2 ), providing an efficient strategy for the preparation of silicon-stereogenic vinylhydrosilanes (Scheme 86).…”
Section: Scheme 84 Co-catalyzed Hydrosilylation Of Internal Alkynesmentioning
confidence: 99%
“…[239] In 2018, Huang and co-workers developed a regio-and enantioselective alkyne hydrosilylation with a pybox-cobalt catalyst (101-CoCl 2 ), providing an efficient strategy for the preparation of silicon-stereogenic vinylhydrosilanes (Scheme 86). [239] In 2018, Huang and co-workers developed a regio-and enantioselective alkyne hydrosilylation with a pybox-cobalt catalyst (101-CoCl 2 ), providing an efficient strategy for the preparation of silicon-stereogenic vinylhydrosilanes (Scheme 86).…”
Section: Scheme 84 Co-catalyzed Hydrosilylation Of Internal Alkynesmentioning
confidence: 99%
“…The scope for the unsaturated substrate is versatile, including alkene,, , alkyne, carbonyl, and carboxylic derivative groups. Additionally, a number of different silanes can be used: much research is performed with phenylsilane, and other silanes such as diphenylsilane, alkyl silanes, and alkoxy silanes, can be employed as well.…”
Section: Introductionmentioning
confidence: 99%
“…However, control of stereo‐ and regioselectivity is the major issue hampering the widespread use of this method, largely because three possible hydrosilylation products, namely α‐, β‐(Z)‐, and β‐(E)‐vinylsilanes, can be generated in the hydrosilylation reaction of terminal alkynes, with the former being rarely obtained selectively . By now, some works about the formation of α‐vinylsilane had been published by theorists and experimenters . By inspection of these researches, we found that the metal‐catalysts were mainly introduced for catalyzing this hydrosilylation of alkynes, such as Co, Pt, and Ru .…”
Section: Introductionmentioning
confidence: 99%
“…Vinylsilanes are valuable building blocks in organic synthesis and material chemistry because of their versatile characters, such as low toxicity, high stability, facile manipulations, and a variety of transformations . Accordingly, methods for the preparation of vinylsilanes have gained increased attentions from synthetic chemists, in which the hydrosilylation of alkynes was considered as a simple and straightforward method . This hydrosilylation reaction involves the addition of a Si − H bond across a C − C triple bond, bringing an atom‐economical result with 100% atom efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation